Choreographing in VR : Introducing ‘Substitute Performers’ as Informants in the Choreographic Process - Pajala-Assefa, Hanna (ACM, 2024)
This paper is situated at the intersection of digital choreography and human-centered interaction within the scope of virtual reality. Both disciplines are discussed under the frame of contemporary artistic practice, an endeavor to make an artistic work while appropriating skills in crafting and composition. The paper focuses on the creation practice in and for virtual reality and the making of an artwork rooted in movement and with a choreographic idea of embedding an improvisatory score into the interaction design. Therefore, the thinking of choreography expands into the design of the interactions in the virtual realm and falls into the subfield of digital choreography. To reflect on the agent-entangled practice of digital choreography within VR and to trace the roles of various performative, epistemic agents active within the creative process, the author introduces a notion of substitute performers. The methods of phenomenology of lived mediated experience and digital choreography are synthesized to optimize the artistic endeavor to design for diverse bodies. These are then combined with various ethnographic methods to provide insights into moving and dancing bodies in a mediated performative realm. These intertwined methods were an elemental part of the creative process of the VR artwork Skeleton Conductor XR Art which was designed to induce pleasure through improvisational engagement and cultivate kinaesthetic awareness.
Keywords: koreografia; tanssi; taiteellinen työ; ihminen-konejärjestelmät; työprosessit; vuorovaikutus; ruumiillisuus; interaktiivinen taide